Melatonin enhances the anti-tumor effect of sorafenib via AKT/p27-mediated cell cycle arrest in hepatocarcinoma cell lines. Issue 34 (18th April 2017) - Long, Fei; Dong, Chengyong; Jiang, Keqiu; Xu, Yakun; Chi, Xinming; Sun, Deguang; Liang, Rui; Gao, Zhenming; Shao, Shujuan; Wang, Liming
Abstract : Proposed model elucidating the role of MT in regulating the proliferation of hepatocellular carcinoma (HCC) cells treated with sorafenib. Abstract : Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide, often diagnosed in late stages when most therapeutic methods are not very effective. The introduction of the multikinase inhibitor sorafenib as the standard of care has opened a window of hope for patients with advanced HCC, patients with very poor prognosis; however, patients usually develop acquired resistance to sorafenib limiting its therapeutic benefits. Melatonin (MT), an indoleamine compound produced in the pineal gland, has shown a substantial beneficial effect in increasing the efficacy of common anticancer drugs and decreasing their toxic effects. Here we demonstrate that MT potentiated the sorafenib-mediated inhibition of cell viability and colony formation in HCC cell lines. Moreover, combined treatment of MT and sorafenib enhanced the cell cycle arrest of HCC cells at the G0/G1 phase. Co-treatment of sorafenib and MT was found to upregulate p27, an inhibitor of several cyclin-dependent kinases (CDK), and downregulate p-AKT, c-myc, cyclin D1 and CDK4/6 protein expression. Furthermore, overexpression of p-AKT using SC79 reversed the effect of sorafenib and MT combination on cell viability and growth of HCC cells. These results suggest that the AKT pathway might be critical for the enhanced anticancer effect observed after co-treatment with MT and sorafenib. Taken together, our findings demonstrated that AKT/p27-mediated cell growth arrest induced by MT increased the sensitivity of HCC cells to the effect of sorafenib.